Genus Thubana Walker of the Malaysian Borneo (Lepidoptera, Lecithoceridae), with Descriptions of Seven New Species - Kyu, Tek Park; Kazuhiro, Sugisima; Fatimah, Abang (Journal of Asia-Pacific Entomology, 2005)
The genus Thubana Walker, 1864 of the Malaysian Borneo is revised. Nine species are recognized including seven new species. The new species are: T. kumatai sp. nov., T. kubahensis sp. nov., T. kinabaluensis sp. nov., T. ochracea sp. nov., T. quadrata sp. nov., T. prolata sp. nov., and T. spinata sp. nov. With regard to the previously known species, photos of adults and the male or female genitalia are given, with some taxonomie notes. A key to the Thubana species of the Malaysian Borneo is provided.